DYNAMICS OF THE ART OF CONTEMPORARY ISLAMIC CALLIGRAPHY ARCHIPELAGO: Comparative Analysis of Malaysian and Indonesian Works - Makmur Harun; Dian Cita Sari; Nur Faaizah Binti Md Adam; Sulaiman Dorloh; Mohd Kasturi Nor Abd Aziz (Journal of Calligraphy, 2022)
The dynamics of contemporary Islamic calligraphy in the archipelago have experienced rapid development after the emergence of institutions and foundations that developed the art, in addition to being often competed at many levels. This is supported by the existence of foundations and institutions, such as the Restu Foundation in Malaysia and the Al-Quran Calligraphy Institute (LEMKA) in Indonesia. In addition, various computer applications and increasingly sophisticated digital systems complement the completeness and beauty of contemporary Islamic calligraphy works of art. The objective of this study is basically to compare the contemporary Islamic calligraphy works produced in the archipelago. Among the aspects that are focused on are the applications and works of contemporary calligraphy that are developing in Malaysia and Indonesia through educational institutions and also their calligraphers. In addition, it describes the types and forms of his works in the two places of study, in addition to the influence, aesthetic value and the use of painting materials through the artist. Focus is also given to the forms and mediums used in producing calligraphy works of art. Furthermore, this study is also expected to find study findings such as a complete discussion of the similarities and differences of contemporary calligraphy art that exists in Malaysia and Indonesia, in addition to a discussion of the subtlety of artistic taste and sharpness of thinking, the artists and their calligraphers. Furthermore, the understanding of the Islamic community in the archipelago gives high respect to this artistic heritage as the best Islamic art for its people. It is also hoped that through this comparative study will manifest Islamic civilization that has been raised through the art of Islamic calligraphy based on the Qur'an and al-Sunnah in Southeast Asia.